ECO E-COMMERCE: REBOOTING ONLINE BUSINESS FOR A GREENER FUTURE - Mazan, Maryna (SWorldJournal, 2025)
The article explores the potential for an ecological transformation of e-commerce to support a sustainable future, with a particular focus on a step-by-step strategy tailored for small and family-run businesses. The aim of the article is to identify how e